Limited mouth opening with a square mandible configuration: a case of masticatory muscle tendon-aponeurosis hyperplasia - Sato, Tsuyoshi (J Surg Case Rep, 2015)
Most clinicians throughout the world are probably unaware of the existence of masticatory muscle tendon-aponeurosis hyperplasia (MMTAH), potentially leading to misdiagnoses such as temporomandibular joint disorder (TMD). Here, we introduce this disease from the viewpoint of education. In February 2013, a 39-year-old woman presented with limited mouth opening. Her facial configuration was characterized by a square mandible. There was no evidence of TMD. Magnetic resonance imaging (MRI) showed bilateral enlargement of the masseter muscles. Additionally, a ‘thick’ aponeurosis of the anterior aspect of the masseter muscle was noted bilaterally. On maximal mouth opening, intraoral palpation along the anterior border of the masseter muscle confirmed a hard cord-like structure, consistent with the findings on MRI. MMTAH was diagnosed. When clinicians notice limited mouth opening on oral examination, they should be knowledgeable about diseases associated with limited mouth opening and a square mandibular configuration, such as MMTAH.